Facial Recognition Technique with Combination Method of Local Binary Pattern Histogram and Image Euclidean Distance. (March 2019) - Erwin,; Saparudin,; Fachrurrozi, M.; Tamaarsa, Alvin; Zhang, Andy
Abstract: This study aims to determine the level of precision, recall, and accuracy of performance of local binary pattern histogram and image euclidean distance for face image recognition. This research uses local binary pattern histogram method for segmenting face image and euclidean distance image for face image recognition. The proposed method started with the process of converting pixel value into a binary value, which then the value is used as a decimal value and the histogram is calculated, for then saved in the database. The trained facial image histogram will be compared with the histogram of the test data using the euclidean distance image formula. The result of this research shows realtime test result get 0.699 recall value and 0.7 precision value.